2021
DOI: 10.1044/2021_jslhr-20-00624
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Perspectives of Siblings of Children With Cochlear Implants

Abstract: Purpose The sibling relationship teaches children to navigate social interactions with their peers. However, the presence of an exceptionality, such as hearing loss, in one child can affect the dynamic of this relationship. This article examines quantitative and qualitative effects of having a brother or sister with a cochlear implant (CI) on siblings with typical hearing (TH) to determine how children with TH perceive their sibling with a CI and how having a CI user in the family affects the sibli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The present study demonstrated no effect of childhood HL on the quantity of vocal turn-taking between the target and the other child in families with and without siblings. These results suggest that both female and male caregivers may exhibit greater sensitivity to childhood hearing loss since they possibly focus more attention on DHH children compared with siblings (Atkins 1987; Gregory et al 1995; Antonopoulou et al 2012; Warner-Czyz et al 2021). However, our results also suggest a positive effect of the child’s assistive device (HA or CI) on sibling or peer interaction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The present study demonstrated no effect of childhood HL on the quantity of vocal turn-taking between the target and the other child in families with and without siblings. These results suggest that both female and male caregivers may exhibit greater sensitivity to childhood hearing loss since they possibly focus more attention on DHH children compared with siblings (Atkins 1987; Gregory et al 1995; Antonopoulou et al 2012; Warner-Czyz et al 2021). However, our results also suggest a positive effect of the child’s assistive device (HA or CI) on sibling or peer interaction.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research presents conflicting evidence on the effect of child disability on the sibling (Schwirian 1976; Israelite 1985; Atkins 1987; Raghuraman 2008) or peer (for review see Antia et al 2003) relationship. Although such studies are limited, the qualitative research suggests a range of results demonstrating negative, positive, or no effect of childhood HL on sibling relationship, probably reflecting the variability of underlying child, parent, and family dynamics factors that might affect study outcomes (Israelite 1985; Atkins 1987; Bat-Chava & Martin 2002; McHale et al 2012; Umat et al 2019; Warner-Czyz et al 2021). Despite these conflicting results, studies consistently demonstrate an improvement of DHH child communication and socialization skills during sibling or peers interaction after receiving an assistice device (Bat-Chava & Deignan 2001; Bat-Chava & Martin 2002; Bat-Chava et al 2005; Umat et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Next to factors within the individual, external factors impact the QoL of siblings, such as good communication within the family and parental availability ( 44 , 46 , 48 , 49 , 54 ). This variety of factors affecting the QoL of siblings is also found in previous reviews with other groups of siblings ( 5 , 33 , 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current scoping review, we found that many studies suggested that parenting-related variables may impact the QoL of siblings. For instance, parental availability and good communication between the family members were often suggested ( 44 , 46 , 48 , 49 , 54 ). However, such variables have hardly been studied empirically.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that in the pediatric population, early and consistent stimulation of the cochlea is critical for the optimal development of speech and language [ 3 , 4 ]. Hearing loss (HL), especially in young children, poses a barrier to education and social integration, as it affects language acquisition, all of which impact total score literacy and the child’s self-esteem and social skills [ 5 , 6 , 7 ]. Untreated hearing loss is often associated with academic underachievement, which can lead to reduced employment opportunities later in life [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%